Construction and validation of an Instrument for Evaluation of Critical Factors in Software Development Projects. - Muller, Felipe Martins; Dal Forno, Gédson Borges (Revista de Administração da UFSM, 2017)
Nowadays a huge number of enterprises make use of Information Systems (IS) in several areas. Since the software is one of the most important IS component it needs to be available and trustful. Lots of effort is invested to study critical factors that affects software development projects results. Survey research is the common technique to obtain the relationship between the variables considered inside the sample. Before the use the surveys must be validated, i.e., if it can measure the right things. This paper shows the steps to validate a survey to be answered by software development professionals. The methodological path is composed by the following steps: literature review, mapping of critical factor in software development, creation of a test survey, application of a initial test, refine and apply the survey, analysis the results throughout statistical methods, concluding the paper with the presentation and analysis of the critical factors found.